ANALISIS PERBANDINGAN ERROR UJI PULSE DAN UJI REGISTER METER KWH SEMI ELEKTRONIK FASA TUNGGAL METODE WAKTU - Anis Nur Indahsari; Galih Setyawan (Hexagon Jurnal Teknik dan Sains, 2020)
A comparative analysis of the pulse test error and the single-phase semi-electronic kWh register meter test was performed. This research is motivated by the amount of time required by the register to display the amount of power consumption must have the same value as the time used to produce the output power of n pulses. The method used in this study is to compare the test time obtained from the blinking of n pulses and the time taken to move the register for n nonius scale with standard time (time obtained from the stopwatch). This study uses a power factor close to 1 using incandescent lamps. The results of the time difference of the pulse test and register test on the research of single-phase electronic phase kWh meter Saint brand with serial number 50579456 using chaosuda stopwatch is 0,13% and 0,18% for Smartphone Stopwatch.